Nanofibrous glass/ceramic porous structures using high-temperature interface bonding. (June 2021) - Stanishevsky, Andrei; Severino, Courtney; Ross, Stacy; Yager, Riley; Armstrong, Micah; Binczarski, Michał; Maniukiewicz, Waldemar; Witońska, Izabela
Highlights: Nanofibrous silica glass/ceramic rigid 3-D shapes are fabricated for the first time. Silica nanofibers with ceramic binder layer are stable up to 1200 °C. Highly porous nanofibrous glass/ceramic can be stronger than microfibrous ceramics. Fiber-binder layer interactions define the properties of glass-ceramic shapes. Abstract: Nanofibrous glass/ceramic rigid shapes with uncommon structures, consisting of electrospun vitreous silica nanofibers coated with 5–30 nm thick Al2 O3 or MgAl2 O4 ceramic layers, were fabricated in this study. Ceramic nanolayers restricted the viscous flow in silica nanofibers and provided strong structural bonding during partial sintering at 1200 °C. The interface interactions between the silica nanofiber core and ceramic nanolayer during sintering defined the resulting microarchitecture, porosity, and phase composition of the material. Nanofibrous glass-ceramic slabs with 90 ± 2% porosity revealed flexural and compressive strengths in the range from 0.7 to 3.2 MPa due to the combined effects of the compounds formed in the silica nanofiber core, ceramic layer, and at their interface. The structural uniformity and mechanical properties of nanofibrous glass/ceramic shapes make them strong alternatives to microfibrous porous ceramics in various applications, especially when a small size of ceramic components is needed.